A new method for interoperability and conformance checking of product manufacturing information. (July 2020) - Peng, Zhiguo; Huang, Meifa; Zhong, Yanru; Chen, Leilei; Liu, Guanghao
Highlights: Semantic representation of product manufacturing information. A unified product manufacturing information ontology. Framework software design for product manufacturing information conformance checking. Abstract: Product manufacturing information (PMI) is the most important information in the product digital model. Whether PMI can be clearly and unambiguous represented and exchanged between different computer-aided software (CAx) has become a topic of high interest in current research. To enhance the interoperability of PMI information among different CAx systems and offer framework software to check the PMI realization ability of different computer-aided design (CAD) software packages, this paper proposes a new method for interoperability and conformance checking by establishing a unified PMI ontology. Using web ontology language description logic (OWL2 DL) and semantic web rule language (SRWL), PMI can be described clearly and without ambiguity and can be read and interpreted automatically by the computer. In addition, the ontology also supplies the functions of consistency checking, knowledge inference, and semantic queries. The analysis shows that this ontology has great engineering significance in realization of PMI interoperability exchange and construction of framework software for PMI conformance checking. Graphical abstract: This paper proposes a new method for interoperability and conformance checking by establishing a unified PMI ontology. Image, graphical abstract